2016
DOI: 10.15557/jou.2016.0008
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostyka ultrasonograficzna w gabinecie lekarza rodzinnego – przegląd piśmiennictwa

Abstract: Ultrasound, which is a safe and non-invasive diagnostic modality that uses more and more advanced imaging techniques, has become the first-choice examination in various diseases. It is more and more often used in the general practitioner's office to supplement physical examination and interview.AimThe aim of this paper is to review the Polish medical literature pertaining to the usage of ultrasound imaging in general practice as well as to present advantages, disadvantages and utility associated with conductin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 1 publication
1
17
0
Order By: Relevance
“…Genc et al [6] and kosiak [5] claim that ultrasound scan performed by a family physician in accordance with the point-of-care principle (i.e., performing the examination and interpreting the result in the course of making a therapeutic decision, in order to confirm the suspected pathology) does not extend the time of the visit, because the time taken for the examination of, for example, the lungs is similar when performed by ultrasound and by stethoscope.…”
Section: Economic Aspects Of Providing Ultrasound Servicesmentioning
confidence: 99%
See 2 more Smart Citations
“…Genc et al [6] and kosiak [5] claim that ultrasound scan performed by a family physician in accordance with the point-of-care principle (i.e., performing the examination and interpreting the result in the course of making a therapeutic decision, in order to confirm the suspected pathology) does not extend the time of the visit, because the time taken for the examination of, for example, the lungs is similar when performed by ultrasound and by stethoscope.…”
Section: Economic Aspects Of Providing Ultrasound Servicesmentioning
confidence: 99%
“…Ultrasonography is a relatively inexpensive, safe, and noninvasive diagnostic tool [2], and its use of dynamic spatial imaging [3] often allows for a diagnosis to be made without the need to perform further imaging tests [4]. as the 'new stethoscope' of a family physician, the ultrasound scanner [5] increasingly contributes to the faster onset of therapy [6] and quicker referral of patients to further diagnosis or specialist care [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…according to Genc et al, a UsG scanner is an element that, apart from the knowledge and skills of the physician, relates to the value of UsG examinations [4]. Gajewicz concluded that buyers should use the guidelines of the Polish UsG society when choosing a UsG scanner, as both the class and age of the equipment determine the quality of the UsG image [20].…”
Section: Cost and Quality Of Usg Scannersmentioning
confidence: 99%
“…Examination results and further diagnosis of patients depend on the professionalism of the UsG operators, their qualifications and experience [4,5]. the royal College of radiologists in the Uk gives advice on UsG training, stating "operators are ethically and legally vulnerable if they have not been adequately trained" [6].…”
Section: Introductionmentioning
confidence: 99%